Change of electrode structure and their destruction in electropulse water treatmen - Shaimerdenova, K.M.; Aitpaeva, Z.K.; Khassenov, A.K.; Kutum, B.B.; Bulkairova, G.A. (Publishing House of the KarSU named after E.A.Buketov, 2017)
The article is devoted to the development and creation of a discharge treatment technology and water activation. The effect of electric discharges on the structure and properties of the electrode system during hydropulse water treatment has been studied. Experimental studies have been conducted to identify disadvantages and advantages of the material cable electrodes. As a result, lengths of destructions of central tendon of electrodes revealed from time of hydropulse treatment. It was found that most effective is the central tendon of electrode, made from a copper.
Keywords: electrode system; hydropulse treatment; electrical discharge